Cost‐effectiveness of population‐based, community, workplace and individual policies for diabetes prevention in the UK. Issue 8 (18th April 2017) - Breeze, P. R.; Thomas, C.; Squires, H.; Brennan, A.; Greaves, C.; Diggle, P.; Brunner, E.; Tabak, A.; Preston, L.; Chilcott, J.
Abstract: Aim: To analyse the cost‐effectiveness of different interventions for Type 2 diabetes prevention within a common framework. Methods: A micro‐simulation model was developed to evaluate the cost‐effectiveness of a range of diabetes prevention interventions including: (1) soft drinks taxation; (2) retail policy in socially deprived areas; (3) workplace intervention; (4) community‐based intervention; and (5) screening and intensive lifestyle intervention in individuals with high diabetes risk. Within the model, individuals follow metabolic trajectories (for BMI, cholesterol, systolic blood pressure and glycaemia); individuals may develop diabetes, and some may exhibit complications of diabetes and related disorders, including cardiovascular disease, and eventually die. Lifetime healthcare costs, employment costs and quality‐adjusted life‐years are collected for each person. Results: All interventions generate more life‐years and lifetime quality‐adjusted life‐years and reduce healthcare spending compared with doing nothing. Screening and intensive lifestyle intervention generates greatest lifetime net benefit (£37) but is costly to implement. In comparison, soft drinks taxation or retail policy generate lower net benefit (£11 and £11) but are cost‐saving in a shorter time period, preferentially benefit individuals from deprived backgrounds and reduce employer costs. Conclusion: The model enables a wide range of diabetes prevention interventions to be evaluated according to cost‐effectiveness, employment and equity impacts over the short and long term, allowing decision‐makers to prioritize policies that maximize the expected benefits, as well as fulfilling other policy targets, such as addressing social inequalities. What's new?: A novel model was developed to help policy‐makers decide which diabetes prevention interventions to pursue, balancing cost‐effectiveness against other objectives, such as equity, employment and short‐term return. Most interventions examined were cost‐saving over a lifetime compared with doing nothing. Individual‐based intervention in high‐risk individuals is likely to be the most cost‐effective option in the long run, whilst population‐ and community‐based interventions are more equitable, reduce employer costs and are cost‐saving over shorter timescales. The model can easily be adapted to evaluate new interventions as they are trialled, and help design local and national diabetes and obesity prevention programmes.